The contextual factors of entrepreneurial intention of college students taking business-related courses in selected colleges/universities in Palo, Leyte and Tacloban City - Anasarias, Kimberly Shane Borata; Castil, Chenny Lorraine Abuda; Lantaco, Alfredo Jr. Cadelina; Ylaya, Czarah Dawn Samillano
Bringing into play the Theory of Planned Behavior (TPB) and the Social Learning Theory (SLT), the present study explores the entrepreneurial intention of students taking business-relatd courses in consideration of three contextual factors; namely entrepreneurial passion, entrepreneurial role models, and entrepreneurial education. The sample (N=314) was identified through a quota sampling technique and is composed of college students from selected universities in Palo, Leyte and Tacloban City. A survey-questionnaire was used for data collection and a descriptive research design was utilized in this study. Consistent with the theories used in the study, the findings reveal that subjective norms and attitude towards enterprise behavior have moderate influence on the entrepreneurial intention of the respondents. However, perceived behavioral control had no particular bearing on the level of entrepreneurial intention of the respondents. The results revealed that there is a significant difference in the level of influence of each contextual factor. Entrepreneurial passion and entrepreneurial education have a moderate influence on entrepreneurial intention of the respondents. On the other hand, entrepreneurial role models had no particular influence. In terms of its correlation, the study found that there is a significant relationship between contextual factors and entrepreneurial intention. Entrepreneurial Passion showed a high positive correlation, Entrepreneurial Role models had negligible correlation, and Entrepreneurial Education has a moderate positive correlation within the context of students who take business-related courses at the se;ected universities and colleges in Palo, Leyte and Tacloban City.